2013
DOI: 10.1101/gr.143677.112
|View full text |Cite
|
Sign up to set email alerts
|

Breakpoint profiling of 64 cancer genomes reveals numerous complex rearrangements spawned by homology-independent mechanisms

Abstract: Tumor genomes are generally thought to evolve through a gradual accumulation of mutations, but the observation that extraordinarily complex rearrangements can arise through single mutational events suggests that evolution may be accelerated by punctuated changes in genome architecture. To assess the prevalence and origins of complex genomic rearrangements (CGRs), we mapped 6179 somatic structural variation breakpoints in 64 cancer genomes from seven tumor types and screened for clusters of three or more interc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
191
0
3

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 166 publications
(207 citation statements)
references
References 50 publications
13
191
0
3
Order By: Relevance
“…CouGaR identified at least one contig (≄3 copies) in 443 of the 467 samples analyzed, and on average we found 6.25 contigs per sample. Interestingly, the 6.25 contigs per sample is nearly twice as many as previously reported (Malhotra et al 2013). The lower number reported earlier could be attributed to both lack of methods that were capable of identifying these CGRs accurately and to the smaller number of samples analyzed.…”
Section: Identification and Characterization Of Cgrs From Tcga Samplessupporting
confidence: 70%
See 3 more Smart Citations
“…CouGaR identified at least one contig (≄3 copies) in 443 of the 467 samples analyzed, and on average we found 6.25 contigs per sample. Interestingly, the 6.25 contigs per sample is nearly twice as many as previously reported (Malhotra et al 2013). The lower number reported earlier could be attributed to both lack of methods that were capable of identifying these CGRs accurately and to the smaller number of samples analyzed.…”
Section: Identification and Characterization Of Cgrs From Tcga Samplessupporting
confidence: 70%
“…It has been previously reported that CGRs are found in 5%-9% of all cancers (Malhotra et al 2013;Zack et al 2013) and ∌25% of bone tumors (Stephens et al 2011). However, these estimates depend on three factors: first, the type of data utilized (array or sequencing); second, the computational method implemented; and third, the specific types of cancer samples analyzed.…”
Section: Identification and Characterization Of Cgrs From Tcga Samplesmentioning
confidence: 96%
See 2 more Smart Citations
“…Except for small insertions, SMASH consistently detected breakpoints with allelic frequencies >1.7%. To see if SMASH produces results comparable to other SV algorithms, we compared its breakpoint detection to HYDRA (Quinlan et al 2010;Malhotra et al 2013) on a set of simulated breakpoints (Supplemental Material; Supplemental Table T3). Overall, SMASH breakpoint detection rates were similar to HYDRA, with SMASH more accurately resolving breakpoint coordinates and HYDRA more consistently detecting short insertions.…”
Section: Resultsmentioning
confidence: 99%